1999
DOI: 10.1592/phco.19.9.760.31547
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Unfractionated Heparin Therapy with Antifactor Xa Activity Results in Fewer Monitoring Tests and Dosage Changes than Monitoring with the Activated Partial Thromboplastin Time

Abstract: Monitoring UFH therapy over 96 hours with an HA assay costs $4.37 more than monitoring with aPTT. This modest increase may be acceptable given other advantages of the HA assay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
45
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 28 publications
0
45
0
Order By: Relevance
“…12 Although we did not directly measure this, we have been notified by many nursing colleagues that our new protocol has led to a decrease in the frequency of dosage adjustments. Such a decrease in the number of laboratory tests may offset the incremental cost increase of the antifactor Xa assay over the aPTT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 Although we did not directly measure this, we have been notified by many nursing colleagues that our new protocol has led to a decrease in the frequency of dosage adjustments. Such a decrease in the number of laboratory tests may offset the incremental cost increase of the antifactor Xa assay over the aPTT.…”
Section: Discussionmentioning
confidence: 99%
“…The functional heparin assay, also known as the antifactor Xa test, is the reference standard for testing the in vivo activity of heparin and has been promoted as a more favorable marker for monitoring a patient's response to heparin. 12,13 The antifactor Xa assay determines heparin activity in a plasma sample after mixing with an excess amount of antithrombin and factor Xa. The amount of unbound residual factor Xa is proportional to the heparin concentration in the plasma sample.…”
mentioning
confidence: 99%
“…The American college of Chest Physicians (ACCP) and the College of American Pathologists (CAP) recommend the use of anti‐Xa, citing that the anti‐Xa values correlate better with heparin concentrations. Studies have shown that monitoring UFH infusion with the anti‐Xa compared with aPTT achieved therapeutic range more rapidly, maintained levels within the goal range for a longer time and required fewer adjustments in dosage and repeated tests . The results of recent studies have raised concern for differences between anti‐Xa and aPTT values and the increased risk of bleeding due to discordant values .…”
Section: What Is Known and Objectivesmentioning
confidence: 99%
“…A therapeutic aPTT range is determined by plotting on a graph simultaneous aPTT and antifactor Xa values from patients receiving heparin, and from the lines of best fit, finding the aPTT values that correspond to 0.3 and 0.7 unit/ml, respectively. With the large degree of variability already known, and the enhanced availability of antifactor Xa automation, some investigators sought to explore if the use of antifactor Xa levels directly for patient care was more feasible than their use in establishing institution‐specific aPTT goal ranges (Table ) …”
Section: Clinical Trials Comparing Activated Partial Thromboplastin Tmentioning
confidence: 99%